Preemergence activity in the greenhouse on Arthraxon quartinianus, of an extract from Pinus sp. - Portuguez-García, Mary Pamela; Agüero-Alvarado, Renán; González-Lutz, María Isabel (Agronomía Mesoamericana, 2020)
Introduction. The pine extract may have herbicidal activity to other plants, affecting seed emergence. Objective. To evaluate the pre-emergent effect of a Pinus sp. extract in a greenhouse. Materials and methods. Two experiments were carried out in the K greenhouse of the Fabio Baudrit Moreno Agricultural Experimental Station (EEAFBM), Universidad de Costa Rica, the first in July and the second between September and October 2018. In the first one, the pre-emergent effect of pine extract, with and without added adherent to the spraying broth, on Arthraxon quartinianus (A. Rich.) and a seed bank containing different species were evaluated; in the second experiment the pre-emergent effect of pine on Amaranthus sp., Ischaemum rugosum Salisb., rice (Oryza sativa), cucumber (Cucumis sativus), and a seed bank was evaluated. For both experiments, a 15 % formulation of pine extract (3.75 kg a.i. ha-1) was sprayed. In both experiments, the number of seedlings emerged was counted, in the first experiment it was recorded at nine days after spraying (das) and in the second at 17 das. Results. The pre-emergent effect on broad-leaved species was not significant, but it was for A. quartinianus (A. Rich.) (p=0,0009). The adherent reduced the effect of the pine extract on A. quartinianus (A. Rich.) (p=0,0116) and other species (p=0,0398). There was an increase in the germination of weeds coming from the seed bank, 121 % for broad-leaved species in general, 92 % for Amaranthus sp. (p=0,013). Besides, the adherent increased the germination of rice seeds by 34 % (p<0,0001). Conclusions. In a greenhouse there was only a significant pre-emergent effect of pine for the weed A. quartinianus (A. Rich.). The pine extract increased the germination of several species.